Caribbean Report 12-02-1999 - The British Broadcasting Corporation; Richards, Ken (anchor, interviewer); Stone Greaves, Keith (correspondent); Fraser, Tony (correspondent); Lee, Chelston (correspondent); Fitzwilliam, Wendy (interviewee) (The British Broadcasting Corporation, 1999)
1. Headlines with anchor Ken Richards (00:26) 2. Anguilla’s Governor Robert Harris is expected to issue a proclamation confirming that general elections will be held on March 4. Chief Minister Hubert Hughes is expected to address the nation on the issue of elections. Nomination day is scheduled for February 23 and more than six thousand Anguillans are eligible to vote. Hubert Hughes Anguilla United Party and its coalition partner the Antigua Democratic Party led by Victor Banks is seeking to win the election. Mr. Banks comments on calls for him to assume a stronger leadership role in the coalition government. Ken Richards reports (00:27- 03:20) 3. Haiti Foreign Minister Fritz Longchamp is defending President René Préval declaration that the term of the parliamentarians has run out and denies that Préval is trying to establish a dictatorship. Mr. Longchamp speaks to anchor Ken Richards on Préval’s move to ensure a free and fair election poll. The issue of the dismissed parliamentarians is expected to go before Haitian courts (03:21 – 05:31) 4. A French judge heading the investigation into the death of Princess Diana has been assigned the civil suits accusing Fidel Castro of crimes against humanity. Chelston Lee reports on French prosecutors initial rejection of the complaints against Fidel Castro and the ensuing action by the Cuban exiles to pursue the matter with the French judge at the helm of the investigation (05:31- 07:04) 5. Ninety-two year old former President of the Dominican Republic Joaquín Balaguer will return from medical treatment in the US to run for the country’s Presidency in 2000. Balaguer remains one of the most important players in the country’s political sphere despite his advancing age and health problems (07:05 - 07:39) 6. West Indies will face arch rivals Australia in an upcoming test series. Keith Stone Greaves interviews the new Australian team captain Steven Waugh on his assessment of the West Indies team and his team’s chances in the upcoming series (07:40 – 10:09) 7. ...